Passive head-up tilt positioning as an early mobilization strategy in neurocritical care: a prospective-retrospective controlled study - Jia, Geng; Feng, Yi; Liu, Zhenwei; Yang, Changchun; Peng, Ya; Shao, Naiyuan (Frontiers in Neurology, 2025)
BackgroundEarly mobilization is recommended in neurocritical care, yet passive mobilization strategies for patients with impaired consciousness remain underexplored. This retrospective matched cohort study, incorporating prospectively collected intervention data, evaluates the clinical efficacy and physiological impact of passive head-up tilt positioning in patients with severe neurological injury.MethodsWe conducted a prospective-retrospective matched cohort study involving 58 patients with traumatic brain injury or hypertensive intracerebral hemorrhage. Twenty-nine patients received standardized passive verticalization using a motorized standing bed; 29 matched controls received standard care. Intracranial dynamics (ICP, CPP, and PRx), respiratory mechanics, intra-abdominal pressure (IAP), and neurological assessments (GCS, CRS-R, ICDSC) were measured at defined intervals. Primary outcomes included NSICU/hospital length of stay, duration of ventilation, complication rates, and long-term functional outcomes.ResultsPassive verticalization was well-tolerated and associated with a significant reduction in ICP (10.62 ± 2.13 vs. 8.38 ± 2.27 mmHg, p < 0.05) without affecting CPP or PRx. Neurological function improved significantly (GCS: 7.90 → 10.07; CRS-R: 8.17 → 12.03; all p < 0.05), and delirium severity declined (ICDSC: 5.97 → 1.62). Intervention patients had shorter NSICU and hospital stays, reduced mechanical ventilation duration, earlier enteral nutrition, lower DVT incidence, and superior 6-month ADL and DRS scores.ConclusionPassive head-up tilt positioning is a safe, feasible early mobilization strategy in neurocritical care. It improves neurological recovery, reduces complications, and supports long-term functional outcomes. These findings support the incorporation of passive verticalization into early rehabilitation protocols for patients unable to engage in active mobilization.